Preparation of selenide catalytic electrode and application of selenide catalytic electrode in industrial flue gas electrochemical carbon capture

By using metal selenide catalytic electrodes in industrial flue gas for electrochemical carbon capture, the problems of catalyst poisoning and low reaction efficiency in the prior art are solved, and efficient carbon dioxide reduction and carbon capture effects are achieved.

CN119455620APending Publication Date: 2025-02-18LANZHOU JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411593430.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art has problems of catalyst poisoning, reduced activity and poor reaction kinetics in direct and efficient electroreduction of carbon dioxide in industrial flue gas, making it difficult to achieve efficient carbon capture and conversion.

Method used

Using metal selenide catalytic electrodes, a selenide catalytic electrode with high active surface area and stable properties is prepared by reacting metal source, selenium source and conductive carbon black under hydrothermal conditions, for industrial flue gas electrochemical carbon capture. set.

Benefits of technology

It significantly improves carbon dioxide reduction efficiency and product selectivity, reduces energy consumption in the electrolysis process, and provides efficient carbon capture and conversion technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005126171150000011
    Figure HDA0005126171150000011
  • Figure HDA0005126171150000012
    Figure HDA0005126171150000012
  • Figure HDA0005126171150000021
    Figure HDA0005126171150000021
Patent Text Reader

Abstract

The invention provides an efficient and economical industrial flue gas electrochemical carbon capture (direct electroconversion of carbon dioxide) catalytic electrode. The electrode is based on selenide, the structure and surface characteristics are optimized through fine treatment, and the electrocatalytic reduction performance of carbon dioxide in industrial flue gas is remarkably improved. In the application, the prepared electrode has a unique oxygen isolation function, avoids the adverse effect of oxygen reduction reaction, shows an excellent carbon capture effect, and can efficiently convert the captured carbon dioxide into chemical products or fuels (such as ethanol, acetic acid and the like) with additional values. In addition, the electrode has good stability, can maintain catalytic performance in long-term use, and meets industrial application requirements. The invention provides an effective electrochemical carbon capture method for reducing the carbon footprint caused by the use of fossil fuel, and has important significance for inhibiting the increase of greenhouse gases and promoting the development of a carbon capture, utilization and sequestration (CCUS) technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of carbon capture, utilization and storage (CCUS), and specifically relates to a metal selenide catalytic electrode and its application in the process of "electrochemical carbon capture of industrial flue gas". Background Art

[0002] About 85% of the world's energy relies on fossil fuels such as coal, and about 75% of the increase in carbon dioxide in the atmosphere comes from the burning of fossil fuels. Excessive use of these fossil fuels will lead to the generation of a large amount of industrial waste gas (i.e. flue gas). In industrial waste gas, the concentration of carbon dioxide can be as high as 20%, which will trigger a greenhouse effect when discharged into the atmosphere. Faced with the carbon dioxide emission control strategies proposed by major economies around the world. Traditional carbon capture methods have the problems of high cost and high energy consumption, making them difficult to promote on a large scale. Electrochemical carbon capture is driven by renewable energy (such as solar energy and wind energy), and can capture and convert carbon dioxide from the air or industrial exhaust gas, with lower energy demand and environmental impact. Such technologies usually do not require expensive chemical reagents, do not produce a lot of heat or by-products, and therefore have the advantages of high efficiency, sustainability, and low cost.

[0003] At present, the use of renewable energy-driven carbon dioxide reduction technology has become one of the most attractive ways to reduce greenhouse gas emissions and promote carbon cycling. In the electrocatalytic reduction of carbon dioxide system, industrial flue gas is directly used as the electrolysis raw material of carbon dioxide, and its capture and conversion are achieved by catalytic electrodes, so that carbon dioxide can be reduced to generate high value-added products, which is of great significance for environmental pollution control. However, due to the complex composition of flue gas, in addition to carbon dioxide, it also contains other impurities (such as oxygen), which will affect the selection of electrode materials and the selectivity of electrochemical reactions, and may cause catalyst poisoning or reduced activity. In addition, the carbon dioxide electroreduction reaction itself is inefficient, and specific catalytic electrodes and reaction conditions are required to improve product selectivity and reaction rate. In the low-concentration carbon dioxide environment of industrial flue gas, the reaction kinetics are poor, which further affects the reduction efficiency. Therefore, to achieve direct and efficient electroreduction of carbon dioxide in industrial flue gas, it is necessary to develop catalytic electrodes that are resistant to impurities, highly selective and highly stable, and optimize the reaction conditions to meet the treatment requirements of low-concentration carbon dioxide.

[0004] The present invention provides a catalytic electrode, which uses industrial flue gas as a carbon dioxide source and utilizes renewable energy electricity to catalyze the conversion of carbon dioxide, effectively inhibits the occurrence of hydrogen evolution reaction and oxygen reduction reaction, has high carbon dioxide reduction efficiency and product selectivity, significantly reduces the energy consumption of the electrolysis process, and provides feasible technical support for carbon capture and conversion in industrial waste gas. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a selenide catalytic electrode and apply the method to electrochemical carbon capture of industrial flue gas.

[0006] To achieve the above object, the present invention adopts the following scheme:

[0007] 1. Preparation of Selenide Catalytic Electrode

[0008] A metal source, a selenium source and deionized water are added with hydrazine hydrate under stirring conditions to prepare solution A. Conductive carbon black is dispersed in deionized water and solution B is formed by ultrasonic treatment. Solution A and solution B are mixed and transferred to a hydrothermal reactor, heated until the reaction is completed, and then a solid product is obtained by centrifugal separation, and washed with deionized water several times. The obtained solid product is then vacuum dried at room temperature. Subsequently, a polymer solution is added to the solid product, and ultrasonic mixing is performed to form a selenide ink. The ink is coated on an electrode substrate and dried to obtain a working electrode loaded with selenide. Next, another polymer solution is mixed with titanium dioxide and added to isopropanol to form a dispersion, and then a certain amount is coated on the working electrode loaded with selenide and dried, and finally a selenide catalytic electrode suitable for electrochemical carbon capture of industrial flue gas is prepared.

[0009] The metal source is a transition metal (copper, silver, tin, cadmium, etc.).

[0010] The selenium source can be selenium powder, selenium oxide, potassium selenate, hydrogen selenide, etc.

[0011] The heat treatment is carried out at 120° C. to 200° C. for 12 to 48 hours.

[0012] The polymer solution can be Nafion, Aemion, Fumion, Sustainion, Aquivion, PiperIon, etc.

[0013] The electrode substrate can be carbon cloth, carbon paper, polytetrafluoroethylene substrate, foamed nickel, foamed copper, etc.

[0014] The amount of the polymer coated on the selenide-loaded working electrode is 0.50 to 4.13 mg·cm -2 .

[0015] 2. Application of electrochemical carbon capture in industrial flue gas

[0016] The electrochemical carbon capture test of industrial flue gas was carried out in a flow cell. The prepared selenide catalytic electrode was used as the working electrode of the cathode. During the reduction process, it is necessary to select a suitable electrolyte and potential window for electrocatalysis.

[0017] The electrolyte can be a pure water solution with electrolytes (such as potassium hydroxide, potassium bicarbonate, etc.), an alcohol aqueous solution (such as ethanol, methanol, etc.), an ionic liquid (such as quaternary ammonium salt, pyrrole salt, etc.), or an organic solvent (such as acetonitrile, acetic acid, etc.).

[0018] The reduction potential window is between -0.5 V and -3.0 V (vs. RHE).

[0019] 3. Characterization of Selenide Catalytic Electrode

[0020] Taking metal selenide AgCu-Se / C as an example, the catalyst is characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), selected area electron diffraction (SAED), scanning electron microscopy (SEM) and corresponding element mapping (EDS mapping).

[0021] (1) XRD characterization

[0022] XRD pattern ( Figure 1 ) shows the crystallization of the AgCu-Se / C catalyst of the present invention. The figure shows that the peak of the catalyst at 25° is attributed to the (002) crystal plane of carbon black. The peaks observed at 32.7° and 34.3° for AgCu-Se / C can be attributed to the (112) and (121) crystal planes (PDF#00-045-1290). The very sharp diffraction peaks indicate that its crystallinity is very high. All XRD results confirm the successful preparation of the AgCu-Se / C catalyst.

[0023] (2) TEM, SEM, SAED and EDS mapping characterization

[0024] Figure 2 TEM, SEM, SAED and EDS mapping images of the AgCu-Se / C catalyst of the present invention at different magnifications. Figure 2 a shows the AgCu-Se / C catalyst as spherical black particles attached to the layered surface of carbon black. These nano-spherical catalysts provide active sites for the reduction of carbon dioxide. Figure 2 b The interface between the carbon layer and AgCu-Se / C and the carbon layer can be vaguely shown. Figure 2 The SAED inset in b shows the typical polycrystalline structure of the AgCu-Se / C catalyst. Figure 2 c, TEM image of AgCu-Se / C shows obvious lattice fringes with a distance of 0.24 nm between adjacent planes, which is slightly smaller than the lattice spacing of Cu-Se / C (220) crystal plane, which may be caused by lattice distortion due to silver doping. Figure 2d shows the SEM image of the AgCu-Se / C catalyst, which exhibits a relatively loose flower cluster shape with a large specific surface area, providing a large contact surface for CO2 reduction. Figure 2 e shows the EDS mapping image of AgCu-Se / C, indicating that the three elements Cu, Se and Ag in the catalyst are uniformly dispersed throughout the carbon black matrix.

[0025] 4. Activity test of selenide catalytic electrode

[0026] In order to illustrate the performance of the prepared selenide catalytic electrode, the activity test is carried out using the metal selenide AgCu-Se / C electrode as an example.

[0027] (1) Electrochemical carbon capture performance test

[0028] Figure 3 (ab) are the electrochemical carbon capture performance test results of the AgCu-Se / C catalytic electrode prepared in the present invention under a pure carbon dioxide atmosphere.

[0029] The specific method of the performance test is to use the AgCu-Se / C catalytic electrode as the cathode working electrode, the platinum sheet as the counter electrode, the Ag / AgCl electrode as the reference electrode, and pure carbon dioxide as the carbon source to construct a three-electrode system in a 0.1M KHCO3 electrolyte to achieve electrochemical carbon capture.

[0030] Figure 3 a It can be seen that the gas phase product contains not only hydrogen, but also a small amount of carbon monoxide and ethylene. The liquid phase product is ethanol and a small amount of formic acid. The total current density gradually increases with the increase of the applied potential. For ethanol, Figure 3 As shown in Fig. 2b, the Faraday efficiency reaches a maximum value (60.9%) at -0.7 V. In addition, the partial current density of ethanol is also shown. At a potential of -1.0 V, the partial current density of ethanol is -1.0 mA cm -2 It reaches a peak at , indicating that the reaction activity of converting carbon dioxide into ethanol is highest at this time.

[0031] Figure 3 (cd) are the electrochemical carbon capture performance test results of the AgCu-Se / C catalytic electrode prepared in the present invention under an atmosphere simulated from industrial flue gas.

[0032] The specific method of the performance test is to use the AgCu-Se / C catalytic electrode as the cathode working electrode, the platinum sheet as the counter electrode, the Ag / AgCl electrode as the reference electrode, simulated industrial flue gas as the carbon source, and construct a three-electrode system in a 0.1M KHCO3 electrolyte to achieve electrochemical carbon capture.

[0033] Figure 3 c It can be seen that the gaseous products contain not only hydrogen, but also very small amounts of carbon monoxide and ethylene, which can be ignored. Ethanol is the only liquid product. At the same time, it can be seen from the figure that the total Faraday efficiency value of carbon dioxide reduction products and hydrogen at different cathode potentials is less than 100.0%. This may be due to the presence of oxygen in the simulated industrial flue gas, which causes the current applied during the electrocatalytic process to be lost to the oxygen reduction reaction with a higher thermodynamic potential. In addition, the oxygen reduction reaction is highly reactive to the copper-based catalyst used to generate multi-carbon products, which may replace some carbon dioxide reduction reactions. Figure 3 d shows the Faraday efficiency and current density of ethanol, the product of carbon dioxide reduction, at different cathode potentials on the AgCu-Se / C catalytic electrode. Compared with pure carbon dioxide conditions, the Faraday efficiency and current density of ethanol decreased slightly in simulated industrial flue gas. With the increase of negative potential, the Faraday efficiency of ethanol increased significantly. It is worth noting that the Faraday efficiency of 53.3% was shown at -0.7V, reaching its maximum value, and the corresponding partial current density of ethanol was -0.7mA·cm -2 At a cathode potential of -1.0 V, the current density of ethanol reached a maximum value of -0.9 mA·cm -2 , indicating that the reaction activity of carbon dioxide to ethanol is highest at this time.

[0034] (2) Stability test

[0035] Stability is also one of the important parameters to measure the catalytic performance of the electrode. Therefore, the stability test of the AgCu-Se / C catalytic electrode was carried out.

[0036] Figure 4 The AgCu-Se / C catalytic electrode prepared by the present invention was subjected to a stability test in a pure carbon dioxide atmosphere.

[0037] The specific method of the stability test is to use the AgCu-Se / C catalytic electrode as the cathode working electrode, the platinum sheet as the counter electrode, the Ag / AgCl electrode as the reference electrode, and pure carbon dioxide as the carbon source, to construct a three-electrode system in 0.1M KHCO3 electrolyte, work for 6 hours at an applied voltage of -0.7V, and take a liquid sample every 1 hour.

[0038] It can be seen that the Faradaic efficiency of ethanol remained above 45.0% during the whole process, while the total current density remained basically unchanged, indicating that the AgCu-Se / C catalytic electrode has good stability.

[0039] Figure 5The AgCu-Se / C catalytic electrode prepared by the present invention is subjected to a stability test in an atmosphere simulating industrial flue gas.

[0040] The specific method of the stability test is to use the AgCu-Se / C catalytic electrode as the cathode working electrode, the platinum sheet as the counter electrode, the Ag / AgCl electrode as the reference electrode, and simulated industrial flue gas as the carbon source, to construct a three-electrode system in 0.1M KHCO3 electrolyte, work for 48 hours at an applied voltage of -0.7V, and take a liquid sample every 1 hour.

[0041] It can be seen that the Faradaic efficiency of ethanol remained above 45.0% during the whole process, while the total current density only decreased slightly, which further demonstrated that the AgCu-Se / C catalytic electrode had good stability.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] 1. Compared with other catalytic electrodes, the selenide catalytic electrode prepared by the present invention has a simpler preparation process and a lower material cost. At the same time, selenides usually have a very stable crystal structure, forming a solid with a layered structure or an ionic crystal structure, which not only makes the physical properties better, but also gives thermal and chemical stability.

[0044] 2. Compared with traditional catalysts, selenium has a larger atomic radius, which increases the active surface area of ​​the metal selenide catalytic electrode, has more accessible catalytic active sites, and improves the activity of carbon dioxide reduction reaction. At the same time, the catalytic electrode of the present invention inhibits the occurrence of oxygen reduction reaction due to the presence of oxygen-isolating ionomers, so that the electrochemical carbon capture under industrial flue gas conditions maintains a high reaction activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 is the XRD pattern of the AgCu-Se / C catalyst of the present invention.

[0046] Figure 2 TEM images of AgCu-Se / C catalyst (ac) at different resolutions; and the inset in (b) corresponds to the SAED image; SEM image (d) and the corresponding EDS mapping image (e).

[0047] Figure 3The carbon capture performance of AgCu-Se / C catalytic electrode was studied. The Faraday efficiency and current density of the cathode product in pure carbon dioxide atmosphere (a); the Faraday efficiency and partial current density of ethanol (b). The Faraday efficiency and current density of the cathode product in an atmosphere simulating industrial flue gas (c); the Faraday efficiency and partial current density of ethanol (d).

[0048] Figure 4 The Faradaic efficiency and current density of ethanol over time for the AgCu-Se / C catalytic electrode in a pure carbon dioxide atmosphere at an applied potential of -0.7 V.

[0049] Figure 5 The Faradaic efficiency and current density of ethanol for the AgCu-Se / C catalytic electrode vary with time at an applied potential of -0.7 V in an atmosphere simulated by industrial flue gas.

[0050] Specific implementation method

[0051] The preparation of the selenide catalytic electrode of the present invention and the electrochemical carbon capture performance of industrial flue gas are further described below through specific examples and comparative examples.

[0052] Example 1

[0053] 5 mmol CuCl2, 2 mmol selenium powder and 50 mL deionized water were added with 5 mL hydrazine hydrate under stirring conditions to prepare solution A. 5 g of conductive carbon black was dispersed in deionized water and solution B was formed by ultrasonic treatment. Solution A and solution B were mixed and transferred to a hydrothermal reactor, kept at 180 ° C for 20 hours, and naturally cooled to room temperature. After that, a black precipitate was obtained by centrifugation and washed with deionized water several times. The obtained black precipitate was then vacuum dried at room temperature. Subsequently, 3 mg of black precipitate and 10 μL Nafion solution were ultrasonically mixed for 30 minutes to form ink. The ink was coated on carbon paper and dried to obtain a working electrode loaded with Cu-Se. Then, 50 μL Fumion solution was mixed with titanium dioxide and 75 μL isopropanol was added. 50 μL of the prepared dispersion was coated on the working electrode loaded with Cu-Se and dried to finally prepare a selenide catalytic electrode suitable for electrochemical carbon capture of industrial flue gas.

[0054] When it was applied to simulate the electrochemical carbon capture of industrial flue gas, the Faradaic efficiency of ethanol at -0.8 V was 68.1% for Cu-Se. In addition, at a constant potential of -0.8 V, the Faradaic efficiency of ethanol was 65.8% after 32 hours of operation, and the current density remained basically unchanged.

[0055] Example 2

[0056] 2mmol CdCl2·2.5H2O, 2mmol selenium powder and 50mL deionized water were added with 6mL hydrazine hydrate under stirring conditions to prepare solution A. 2g conductive carbon black was dispersed in deionized water and formed solution B by ultrasonic treatment. Solution A and solution B were mixed and transferred into a hydrothermal reactor, kept at 140℃ for 12 hours, and naturally cooled to room temperature. After that, a black precipitate was obtained by centrifugation and washed with deionized water several times. Then the obtained black precipitate was vacuum dried at room temperature. Subsequently, 0.5mg black precipitate and 30μL Nafion solution were ultrasonically mixed for 30 minutes to form ink. The ink was coated on carbon paper and dried to obtain a Cd-Se loaded working electrode. Then, 40μL Sustainion solution was mixed with titanium dioxide and 75μL isopropanol was added. 50μL of the prepared dispersion was coated on the Cd-Se loaded working electrode and dried to finally prepare a selenide catalytic electrode suitable for electrochemical carbon capture of industrial flue gas.

[0057] When applied to simulated industrial flue gas electrochemical carbon capture, the Faradaic efficiency of Cd-Se for carbon monoxide at -0.8 V was 48.2%. In addition, at a constant potential of -0.8 V, the Faradaic efficiency of carbon monoxide was 45.6% after 12 hours of operation, and the current density remained basically unchanged.

[0058] Example 3

[0059] 4mmol InCl3·4H2O, 0.5mmol AgNO3, 3mmol selenium powder and 50mL deionized water were stirred and added with 5mL hydrazine hydrate to prepare solution A. 6g conductive carbon black was dispersed in deionized water and formed into solution B by ultrasonic treatment. Solution A and solution B were mixed and transferred into a hydrothermal reactor, kept at 180℃ for 12 hours, and naturally cooled to room temperature. After that, a black precipitate was obtained by centrifugation and washed with deionized water several times. Then the obtained black precipitate was vacuum dried at room temperature. Subsequently, 0.5mg black precipitate and 30μL Nafion solution were ultrasonically mixed for 30 minutes to form ink. The ink was coated on carbon paper and dried to obtain a working electrode loaded with AgIn-Se. Then, 60μL Aquivion solution was mixed with titanium dioxide and 75μL isopropanol was added. 100μL of the prepared solution was coated on the working electrode loaded with AgIn-Se and dried to finally prepare a selenide catalytic electrode suitable for electrochemical carbon capture of industrial flue gas.

[0060] When it was applied to simulate the electrochemical carbon capture of industrial flue gas, the Faradaic efficiency of ethanol of AgIn-Se was 68.7% at -0.8 V. In addition, at a constant potential of -0.8 V, the Faradaic efficiency of ethanol was 61.4% after 22 hours of operation, and the current density remained basically unchanged.

[0061] Comparative Example 1

[0062] The heating temperature of the hydrothermal reactor in the preparation step of the selenide catalytic electrode was adjusted to 100° C. and maintained for 20 hours. Other operations were the same as in Example 1 to obtain a selenide catalytic electrode.

[0063] The activity of the prepared catalytic electrode was characterized: for the prepared selenide catalytic electrode, when it was used to simulate the electrochemical carbon capture of industrial flue gas, the ethanol Faraday efficiency reached only 18.5% at -0.8V.

[0064] This is because the heating temperature of the hydrothermal reactor is too low, resulting in insufficient temperature and pressure, so that the generated material fails to form a certain crystal and the structure is damaged, which in turn affects the activity of the catalytic electrode.

[0065] Comparative Example 2

[0066] The amount of polymer applied to the selenide-supported working electrode in the selenide catalytic electrode preparation step was adjusted to 5.00 mg cm -2 , other operations are the same as those in Example 2 to obtain a selenide catalytic electrode.

[0067] The activity of the prepared catalytic electrode was characterized: for the prepared selenide catalytic electrode, when it was used to simulate the electrochemical carbon capture of industrial flue gas, the carbon monoxide Faraday efficiency at -0.8V only reached 8.2%.

[0068] This is because too much polymer solution is applied to the selenide-loaded working electrode, which not only hinders the transmission of oxygen, but also the transmission of carbon dioxide, thereby affecting the activity of the catalytic electrode.

Claims

1. A method for preparing a selenide catalytic electrode, comprising the following steps: A metal source, a selenium source and deionized water are added with hydrazine hydrate under stirring conditions to prepare solution A. Conductive carbon black is dispersed in deionized water and solution B is formed by ultrasonic treatment. Solution A and solution B are mixed and transferred to a hydrothermal reactor, heated until the reaction is completed, and then a solid product is obtained by centrifugal separation, and washed with deionized water several times. The obtained solid product is then vacuum dried at room temperature. Subsequently, a polymer solution is added to the solid product, and ultrasonic mixing is performed to form a selenide ink. The ink is coated on an electrode substrate and dried to obtain a working electrode loaded with selenide. Next, another polymer solution is mixed with titanium dioxide and added to isopropanol to form a dispersion, and then a certain amount is coated on the working electrode loaded with selenide and dried, and finally a selenide catalytic electrode suitable for electrochemical carbon capture of industrial flue gas is prepared.

2. The method for preparing a selenide catalytic electrode according to claim 1, characterized in that: The metal source in the step is a transition metal (copper, silver, tin, cadmium, etc.).

3. The method for preparing a selenide catalytic electrode according to claim 1, characterized in that: The selenium source in the step can be selenium powder, selenium oxide, potassium selenate, hydrogen selenide, etc.

4. The method for preparing a selenide catalytic electrode according to claim 1, characterized in that: The heat treatment in the step is to react at a temperature of 120° C. to 200° C. for 16 to 48 hours.

5. The method for preparing a selenide catalytic electrode according to claim 1, characterized in that: The polymer solution in the step can be Nafion, Aemion, Fumion, Sustainion, Aquivion, PiperIon, etc.

6. The method for preparing a selenide catalytic electrode according to claim 1, characterized in that: The electrode substrate in the step can be carbon cloth, carbon paper, polytetrafluoroethylene substrate, foamed nickel, foamed copper, etc.

7. The method for preparing a selenide catalytic electrode according to claim 1, characterized in that: The amount of polymer applied to the selenide-loaded working electrode in the step is 0.50 to 4.13 mg·cm -2 .

8. A selenide catalytic electrode as claimed in claim 1 is applied to electrochemical carbon capture of industrial flue gas, the steps are as follows: the flue gas generated by industrial coal combustion, etc. is purified by industrial desulfurization, denitrification and dust removal processes, and the final carbon dioxide content is 7-15%. The prepared selenide catalytic electrode is used in an electrolytic cell to capture industrial flue gas carbon. During the reduction process, a suitable electrolyte and potential window need to be selected for electroconversion.

9. The use according to claim 8, characterized in that: The electrolyte in the step can be a pure water solution added with electrolytes (such as potassium hydroxide, potassium bicarbonate, etc.), alcohol aqueous solution (such as ethanol, methanol, etc.), ionic liquid (such as quaternary ammonium salt, pyrrole salt, etc.), organic solvent (such as acetonitrile, acetic acid, etc.).

10. The use according to claim 8, characterized in that: The potential window in the steps is in the range of -0.5V to -3.0V (vs. RHE).